PERAN PEREMPUAN PENGRAJIN BAMBU DALAM MENINGKATKAN PENDAPATAN KELUARGA DI DESA LOYOK KECAMATAN SIKUR KABUPATEN LOMBOK TIMUR - Susilawati, Susilawati; Aini, Qurratul; Sholihah, Isfi; Lestari, Reni (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
This study aims to determine the shape of the role played by women artisans in increasing family income, and to determine the level of success of women artisans in increasing that income.This research is a qualitative descriptive study that focuses on how the role and level of success of women craftsmen in increasing family income in Loyok Village, Sikur District, East Lombok Regency. This study uses two types of data namely primary data and secondary data. Data collection techniques used were observation, interviews and documentation. While the data analysis techniques used in this study are data collection, data reduction, data presentation, and conclusions.The results showed several forms of the role of women in increasing family income, namely the role of breadwinners (public) and the role of households (domestic), while the success rate of the role of women working as bamboo craftsmen ranged from 30-50% with an average contribution of 36 % This means that this woman who is a bamboo craftsman has quite an important role in increasing her family's income